Comparative effectiveness of neutral and plantarflexion position training in male adolescent soccer players with lateral ankle sprain - Xiangxiang Dou; Yonghwan Kim; Munku Song (Journal of Men's Health)
Background: Lateral ankle sprain (LAS) is a common recurring injury among soccer players, often associated with weakness in the peroneus longus and peroneus brevis muscles and impaired balance. However, research on the effects of different training interventions on these muscles is limited. This study aimed to compare the effects of two distinct training interventions on the peroneus longus and peroneus brevis muscles, focusing on ankle positioning during the training. Methods: Fifty-six male high school soccer players (age: 16.3 ± 1.1 years; playing career: 6.1 ± 1.4 years) with recurrent LAS were recruited from 15 first-division soccer clubs. They were randomly assigned to either a neutral position training (NPT) with 0° group (n = 28) or a plantarflexion position training (PPT) with 40–50° group (n = 28). Both groups underwent an 8-week home-based training program with mobile monitoring. Pre- and post-intervention assessments included Foot and Ankle Outcome Scores (FAOS), ankle strength, dynamic balance and hop tests. Results: it showed significant improvements in FAOS, ankle strength, balance and hop tests for both groups (p < 0.05). Notably, the PPT group demonstrated significantly greater improvements in dynamic balance and hop test performance compared to the NPT group. Specifically, the distance in the dynamic balance test increased from 68.9 ± 4.2 to 73.6 ± 3.8 cm in the NPT group and from 69.5 ± 3.6 to 79.4 ± 3.5 cm in the PPT group (p < 0.001). The single hop distance improved from 132.4 ± 20.3 to 152.0 ± 13.1 cm in the NPT group and from 129.3 ± 17.0 to 172.9 ± 11.0 cm in the PPT group (p < 0.001). Conclusions: while both PPT and NPT interventions were effective in enhancing outcomes for adolescent soccer players with LAS, PPT led to more pronounced improvements in dynamic balance and hop test performance.